COVID-19, the Reality of an Internal Medicine Ward - Gomes da Cunha, Joana; dos Santos Almeida , Rita; dos Santos Pereira, Sofia; Veiga, Ricardo; Costa, Marta; Romão, Vera (Portuguese Journal Internal Medicine, 2024)
Introduction: The reorganization of health care imposed by the COVID-19 pandemic revealed the work capacity of all health professionals, mirroring the fundamental role of Internal Medicine. This work intended to highlight the complexity of managing the COVID-19 patient, often guided by the absence of theoretical/scientific support in the face of the unknown. Methods: A retrospective and descriptive evaluation of all patients with SARS-COV2 infection admitted to a ward of the Internal Medicine service, Unidade Local de Saúde de Viseu Dão-Lafões (ULS Viseu Dão-Lafões), in the period between January-April and July-November 2021 (pandemic peaks of 2021). Results: During the nine months under study, 394 patients were evaluated, with a predominance of males 56.60% (n = 223) and an average age of 70.42 years. The average length of stay was 13.95 days. Most had at least one cardiovascular risk factor, and only 29.44% (n = 116) were vaccinated against COVID-19. Of the therapy, 84.26% (n = 332) received dexamethasone, 85.79% (n =3 38) needed supplemental oxygen therapy; approximately 22.08% (n = 87) required non-invasive mechanical ventilation, and 7.61% (n = 30) underwent invasive mechanical ventilation/high-flow oxygen therapy. There were 23.86% (N = 94) deaths. COVID-19 infection was the primary diagnosis in most patients, but many were secondary diagnoses. Conclusion: The severity and complexity of an unknown nosological disease, in the pandemic phase, is of enormous professional and personal demand, as represented by the characterization of this sample. The spectrum of critically ill patients in need of mechanical ventilatory support stands out, in an admissions curve that turned out to be exponential.